(untitled) - Diaz Alvarez, J.A.=700 1 Brown Manrique, O.; Rodriguez Alonso, R.; Alujas, D.; Herrera Isla, L.
(En, Es)
ilus., 10 ref.
Influencia del regimen de riego en la incidencia de la mancha grasienta (Mycosphaerella citri Whiteside)
Keywords: MYCOSPHAERELLA CITRI; HONGOS; RIEGO; CUBA; MANCHA GRASIENTA; REGIMENES DE RIEGO